Rivaroxaban Precision Dosing Strategy for Real‐World Atrial Fibrillation Patients - Robyn Konicki; Daniel Weiner; J. Herbert Patterson; Daniel Gonzalez; Angela Kashuba; Yanguang Carter Cao; Anil K. Gehi; Paul Watkins; J. Robert Powell (Wiley, 2020)
Rivaroxaban is a direct‐acting oral anticoagulant approved to prevent strokes in patients with atrial fibrillation. Dosage recommendations are approved for all adult patients to receive either 15 mg or 20 mg once daily depending upon renal function. There are a number of reasons to believe rivaroxaban dosing could be more effective and/or safer for more patients if increased dosing precision is available. Because real‐world patients are more diverse than those studied in phase III clinical trials, we evaluated the extremes of creatinine clearance (CrCl) on rivaroxaban clearance using a published population pharmacokinetic model and applying exposure variation limits (±20%) based on published literature. The proposed dosing recommendations are 10 mg once daily (CrCl 15-29 ml/min), 15 mg once daily (CrCl 30-69 ml/min), 10 mg twice daily (CrCl 70-159 ml/min), and 15 mg twice daily (CrCl 160-250 ml/min). These new dosing recommendations should be prospectively tested for predictive accuracy and to assess the impact on AF patient efficacy and safety.